Lactobacillus casei addition to a repletion diet-induced early normalisation of cytokine profils during a pneumococcal infection in malnourished mice - Salva, Maria Susana (2008)
This work studied the influence of Lactobacillus casei on cytokine production during repletion of malnourished mice in the face of an infectious challenge. In addition, the number and function of cells involved in the immune response against a respiratory infection was evaluated. Weaned mice were malnourished after consuming a protein-free diet (PFD) for 21 days. Malnourished mice were fed a balanced conventional diet (BCD) for 7 days or BCD for 7 days with L. casei supplementation on day 6 and day 7 (BCD+Lc). The malnourished control group (MNC) received PFD while the well-nourished control (WNC) mice consumed BCD. Mice were challenged intranasally with Streptococcus pneumoniae at the end of each dietary treatment. Malnutrition impaired the levels of serum tumor necrosis factor (TNF)-α and interleukin (IL)-1β, IL-4, IL-6 and IL-10. In addition, neutrophil number and activity, lymphocyte maturation and bone marrow CD4+, CD8+ and CD19+ cells number, were also impaired in the MNC group. Repletion with BCD induced a slight improvement in some of the parameters studied. However, when L. casei was added to the BCD, a normalisation of TNF-α, IL-1β and IL-6 values after infection and an increase in the levels of IL-10 and IL-4 compared to the WNC group was observed. Moreover, BCD+Lc induced a significant improvement in blood and bone marrow cells. Consequently, the use of L. casei as a supplement in a repletion diet was associated with a pattern of inflammatory and anti-inflammatory cytokines that led to an increased number and functionality of the cells that participate in the immune response against a pneumococcal infection.